Analisis Pangsa Pasar Produk Indonesia Melalui Perjanjian Indonesia-Japan Economic Partnership Agreement (IJEPA) - Wati, Annisa Eka; Puteri, Indah Febriyanti Fatmah; Lazuardi, Muhammad Rizqy; Maksum, Mutiara Ainurrahmah; Taryana, Valentine Yusrin Susanti; Huy, Nguyen Thanh (Journal of Economics and Management, 2023)
Every country conducts international trade to meet domestic needs which cannot be met due to limitations in fulfilling their needs. However, in practice, international trade has barriers in the form of tariffs and non-tariffs, this is the background for the governments of each country to reduce trade barriers by creating Free Trade Agreements (FTAs). One of the FTAs imposed by Indonesia, namely the Indonesia-Japan Economic Partnership Agreement (IJEPA), is a bilateral free trade economic cooperation agreement that was first carried out by Indonesia and Japan as one of its trading partner countries. In order to analyze the influence of the implications of IJEPA on international trade, especially on the opportunities for the share of Indonesian products in the Japanese market, a research was carried out using a quantitative approach and a review of the literature. The results of this analysis indicate that if Indonesia can take advantage of all available opportunities and facilities, Indonesia can expand and strengthen the market share of Indonesian products or commodities to the Japanese market through IJEPA.